Você deve lutar pela xepa da feira e dizer que está recompensado: Evidências da plataformizaç\~ao e a precarizaç\~ao do trabalho no Brasil - Sandro Sacchet de Carvalho; Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article, using data from the Pesquisas por Amostra de Domicílios (PNAD) and the PNAD Contínua, it shows that the platformization of the occupations of passenger transport drivers and deliverers/motorcycle couriers has increased the participation of the transport and postal sector in the Brazilian economy, as well as contributing significantly to the recent rise of self-employed workers. In addition, the expansion of platform workers clearly represents a process of precarization, with lower incomes, less formalization, lower social security contributions and longer working hours. We also take advantage of the recent release of the "Pesquisa Nacional por Amostra de Domicílios Contínua: Teletrabalho e trabalho por meio de plataformas digitais 2022" to establish a more accurate and complete picture of the characteristics of platform work and corroborate the process of precarization brought about by the platformization of work.
Keywords: E26; J46; J81; J83; O17; 330; labor precarization; Self-employed work; Worker's rights